Social and Religious Behavior of Drug and Alcohol Users - Pauji Pauji (The International Journal of Politics and Sociology Research, 2022)
Marriage is forming a family with the opposite sex, or also having sex or having intercourse which is a contract that causes lawful association and cooperation between men and women throughout life, whose rights and obligations have been regulated by Shari'ah law. While drugs are types of illegal drugs that cause users to become unconscious. There are many types of drugs, including marijuana, heroin, morphine, cocaine. The use of illegal drugs is severely punished by the government, and in Islamic law it is also strictly prohibited. While liquor is a drink that can intoxicate the drinker, and is forbidden in Islam. The object of this research is the informants who consume drugs and alcohol, then they decide to get married. In this study the authors tried to find out the effect of marriage on drug and alcohol users. Based on the results of the study, it can be concluded that marriage can have a positive effect on drug and alcohol users; both morally and socially because it can avoid living patterns of deviant behavior, such as prostitution, freesex, malak/nodong and stealing. Drugs and alcohol are very detrimental to health, for example, for a drug/alcohol user physically he will experience heart palpitations, hypertension and even lead to death. Marriage is able to provide good education in mental and spiritual formation and good morals for those who run it. for a drug/alcohol user physically he will experience heart palpitations, hypertension and even lead to death. Marriage is able to provide good education in mental and spiritual formation and good morals for those who run it. for a drug/alcohol user physically he will experience heart palpitations, hypertension and even lead to death. Marriage is able to provide good education in mental and spiritual formation and good morals for those who run it.